Impact of Doping on Charge Transport Properties in Thienothiophene‐Based Organic Porous Polymers - Melis Unal; Recep Isci; Ilknur Demirtas; Erdal Ertas; Wakana Matsuda; Sailun Ji; Takayuki Tanaka; Yusuke Tsutsui; Shu Seki; Turan Ozturk (Macromolecular Materials and Engineering)
Abstract Organic covalent frameworks (COFs) have played significant roles in achieving high performance as electronic conductive and semi‐conductive materials in a wide range of applications, including solar cells, capacitors, hydrogen‐production or storing materials, cancer cell treatments, photosensitizers in bacterial therapy, chemical sensors, and light‐emitting diodes. Organic porous polymer materials are analogs of COFs without crystalline nature and widely examined in material chemistry owing to their ease of design, functionality, and flexibility. Novel conjugated triazine‐type organic porous polymers (P1‐P3), possessing 2‐benzonitryl‐3‐(4′‐methoxyphenyl)thieno[3,2‐b]thiophene (TT) as a π‐bridge and triphenylamine (TPA), tetraphenylethylene (TPE) and carbazole (Cbz) as linkers are designed and synthesized via trimerization reaction using trifluoromethanesulfonic acid (CF3SO3H). The study examined the electronic and optical properties of the monomers (M1‐M3), surface morphologies, and photoconductive behaviors of the polymers using various techniques such as UV–vis and fluorescence spectroscopies, CV, SEM, BET, and FP‐TRMC. Among the investigated porous polymers, the polymer (P3) having a Cbz‐linkage exhibited the highest photoconductivity φ∑µ, both undoped (1.8 × 10−9 m2 V−1 s−1) and I2‐doped (3.2 × 10−8 m2 V−1 s−1). The conductivity went down to φ∑µ = 8.5 × 10−10 m2 V−1 s−1 (undoped) and 1.5 × 10−8 m2 V−1 s−1 (I2‐doped) with the polymer (P2) having a TPE‐linkage.